Hunting patterns of the Iban community of Kampung Sebandi and the status of wildlife populations in Sebandi Forest - Nafisah, Bt. Tahir (Universiti Malaysia Sarawak (UNIMAS), 2004)
Hunting is one of a human activity, which involved the harvesting of wildlife from their habitat for human use. They are for nutritional, trade, culture and religion, and economic purposes. Hunting in the Tropics today are less sustainable due to harvesting of wildlife exceeds their reproduction rate and also habitat loss. This study was conducted to elucidate the hunting patterns of the Iban community of Kampung Sebandi (N 01°36.257', E 109°51.087') in relation to wildlife population density and abundance in Sebandi Forest (N OJ036.920', E 109°50.823'). The results revealed that the main reason for hunting is for subsistence, besides sport and to reduce crop pest problems. Huntings were done during the days and night in group of three to hunters. Day hunting activities were preferred and done by using shotguns and accompanied by dogs. The index of hunting pressure in Sebandi Forest was 98.14. There were three types of animals usually hunted which included bearded pig (Sus barbatus). sambaI' deer (Cen.'us 11.nZ:color) dan lesser mousedeer (Tragulus javanicus). During the study period, the mammals hunted were lesser mousedeer, common palm civet (Paradoxurus hennaphroditus) and sambar deer with biomass of 71.~37%, 22.18% and 6.62% respectively. Study on wildlife density and abundance in Sebandi Forest was done by usmg line transect method. A total of 49 individuals of mammals representing 11 species and 10 families were recorded. The Families include Insectivore, Scandentia, Dermoptera, Primates, Pholidota, Rodentia, Carnivora, and Artiodactila. The dominant species was Plaintain squirrel (Callosciurus notatu.s) with 16 individuals or 561 individual per 100 km2 with relative abundance of 32.65%. This is followed by sambaI' deer with 12 individuals or 421 individual per 100 km2 with relative abundance of 24.49%. There were 157 birds representing 45 species and 23 families. The families include Accipitridae, Rallidae, Columbidae, Psittacidae, Cuculidae, Strigidae, Caprimulgidae, Alcedinidae, Megalaimidae, Picidae, Eurylaimidae, Aegithinidae, Pycnonotidae, Turdidae, Timaliidae, Sylvidae, Muscicapidae, Dicaeidae, Nectariniidae, Sturnidae, Estrildidae, Dicruridae and Corvidae. The Sebandi Forest \vas dominated by red-throated barbet (Meg-alaima mystacophanos) and rufous-tailed tailorbird (Orthotomu.s sericeu.s) 10 individual or 3.50 individual per kilometer2 and 6.369% of relative abundance, The study on wildlife diversity between the disturbed (secondary forest) and disturbed (plantations) areas of Sebandi Forest showed that there was a significant different of mammals diversity with Shannon-Weiner Index of HI = 3.322 and H2 2.000 each. However, there was no significant difference with regard to bird diversity between the two areas. From the overall result obtained, the lower the numbers of wildlife recorded in the numbers of species hunted, the higher their numbers recorded during the wildlife survey. For example, there were nine individuals of lesser mousedeer hunted, thus the number of this species was low with only one individual recorded during the wildlife survey in Sebandi Forest. And so as for both bearded pig and sambaI' deer.